2022
DOI: 10.3390/vaccines10050733
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical and Laboratory Findings and Outcomes of Hospitalized COVID-19 Patients Who Were Either Fully Vaccinated with Coronavac or Not: An Analytical, Cross Sectional Study

Abstract: COVID-19 vaccines are highly protective against severe disease; however, vaccine breakthrough infections resulting in hospitalization may still occur in a small percentage of vaccinated individuals. We investigated whether the clinical and microbiological features and outcomes were different between hospitalized COVID-19 patients who were either fully vaccinated with Coronovac or not. All hospitalized COVID-19 patients who had at least one dose of Coronavac were included in the study. The oldest unvaccinated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…In the study of Mahajan et al [ 16 ], where they evaluated vaccinated and unvaccinated patients with a positive SARS-CoV-2 PCR test, they found that the CT-SS of vaccinated people was mild-moderate, while unvaccinated individuals were moderate-severe. Again, in the studies conducted by Russo et al [ 4 ], Ravindra et al [ 5 ], Fatima et al [ 6 ], and Yavuz et al [ 17 ], when the CT SS of vaccinated and unvaccinated patients were compared, it was shown that vaccinated patients had milder pulmonary involvement. In our study, it was shown that unvaccinated individuals had moderate-severe lung involvement, and patients who received two doses of CoronaVac or two doses of BioNTech or three doses of vaccine had moderate lung involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Mahajan et al [ 16 ], where they evaluated vaccinated and unvaccinated patients with a positive SARS-CoV-2 PCR test, they found that the CT-SS of vaccinated people was mild-moderate, while unvaccinated individuals were moderate-severe. Again, in the studies conducted by Russo et al [ 4 ], Ravindra et al [ 5 ], Fatima et al [ 6 ], and Yavuz et al [ 17 ], when the CT SS of vaccinated and unvaccinated patients were compared, it was shown that vaccinated patients had milder pulmonary involvement. In our study, it was shown that unvaccinated individuals had moderate-severe lung involvement, and patients who received two doses of CoronaVac or two doses of BioNTech or three doses of vaccine had moderate lung involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the effectiveness of the CoronaVac vaccine and hospitalizing 292 patients diagnosed with COVID-19, no significant difference was found between the acute phase reactants of vaccinated and unvaccinated patients[ 17 ]. In another study conducted in Poland, no significant difference was found between acute phase reactants[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that COVID-19 patients with underlying diseases have increased risk of poor prognosis (15)(16)(17)(18). In the study of Yavuz et al, chronic pulmonary disease, malignancy, chronic kidney disease, and cardiovascular diseases were reported as independent risk factors for mortality (17).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that COVID-19 patients with underlying diseases have increased risk of poor prognosis (15)(16)(17)(18). In the study of Yavuz et al, chronic pulmonary disease, malignancy, chronic kidney disease, and cardiovascular diseases were reported as independent risk factors for mortality (17). In the study by of Sezen et al, mortality was found to be significantly higher in patients with CCI ≥ 1 (18); however, there is a limited number of studies evaluating the effect of comorbid diseases on prognosis in patients with CoronaVac.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils can mediate the vaccination- and specific antibody-associated side effects such as thrombosis [ 15 ]. At the same time, vaccination and RBD-specific antibodies prevent the COVID-19-associated severe inflammation and complications, some of which are mediated by neutrophils [ 16 ]. Thus, the effects of SARS-CoV-2 antigen-specific antibody induction on neutrophils are an important but poorly investigated.…”
Section: Introductionmentioning
confidence: 99%